"There's so much more to that sinking island!"—Restorying migration from Kiribati and Tuvalu to Aotearoa New Zealand. Issue 3 (24th August 2022) - Yates, Olivia E. T.; Groot, Shiloh; Manuela, Sam; Neef, Andreas
Abstract: Background and Aims: Many Pacific people are considering cross‐border mobility in response to the climate crisis, despite exclusion from international protection frameworks. The 'Migration with dignity' concept facilitates immigration within existing laws but without host government support. Through the metaphor of Pacific navigation, we explore the role of dignity in the lives of I‐Kiribati and Tuvaluans in Aotearoa New Zealand. Methods: Combining talanoa (pacific research method) with I‐Kiribati and Tuvaluan community members, alongside critical community psychology and thematic analysis, we depict climate mobility as a wa or vaka moana (ocean‐going canoes) journey. Analysis: Participants are expert navigators, navigating immigration obstacles to (re)grow their roots in Aotearoa New Zealand before charting a course for future generations to thrive. They draw strength from culture and community to overcome the adversity of precarious living and visa non‐recognition. Conclusion: Reconceptualising climate mobility through a Pacific lens imagines both dignity and cultural preservation as possible, despite the indignities and limitations of socio‐political systems and protections for climate migrants.